ANALISIS FENOMENA GOLONGAN PUTIH PADA PEMILIHAN GUBERNUR JAWA TENGAH 2013 - Nuri Mukti Yuda Wibawa; Hermini S; Susilo Utomo (Journal of Politic and Government Studies, 2014)
The phenomenon of swing voters in every election in Indonesia is quite interesting to study. Central Java is one of the provinces with a high non-vote behavior rate. Pati District, in Wonogiri District, Temanggung District a county with a high level of non-vote behaviour, moderate, and low in Central Java Province. non-vote behaviour can be regarded as a form of democratic failure. non-vote behaviour when linked with the